POSSIBILITIES OF DEVELOPMENT OF BUSINESS IN THE SPHERE OF THE MOTOR TRANSPORT - E. Kuptsova; A. Kondratyev (Вестник университета, 2016)
Thе article contains the description of opportunities: reduction of negative impact of the motor transport on environment, decrease in cost of transportation of goods and passengers by motor transport, updating of park of vehicles in the conditions of crisis when the state sources of financing can be limited. Also article contains a list of the parties interested in implementation of the projects directed on achievement of the specified purposes, and the conceptual scheme of their interaction.